Craig and Kalam Cosmological Argument - Tavacoli, Gh (Comparative Theology, 2011)
Among different arguments for the existence of God the Kalam cosmological argument is a very famous one which is elaborated by Professor William lane Craig. Craig claims that the universe began to exist, then he continues to say: everything that begins to exist has a cause and therefore the universe has a cause. But how do we know that the universe began to exist? This premise forms the most important part of Craig’s contention, and he bolsters it by four arguments, the first two are driven from philosophy and the other two, which he prefers to name them “confirmations from sciences” are driven from sciences; the first one evokes to big bang theory and the seconds to the second principle of thermodynamic which are respectively adopted from cosmology and physics.In this essay we are going to survey Craig’s arguments and estimate their value and weight.